STRATEGI PEMASARAN MAKANAN RINGAN DI MASA PANDEMI MELALUI SOSIAL MEDIA INSTAGRAM STUD I KASUS : OUTLET DONUTDAY BOYOLANGU, TULUNGAGUNG - Arlisa Dhealita Suwoto; Achmad Sjamsudin (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
MSMEs in Indonesia are one of the spearheads of economic stability in Indonesia. Because this business has a very stable development, therefore the government must take part in the development of MSMEs in Indonesia so that they can maintain economic stability in this country. bankrupt business. Because they are unable to survive due to limited mobilization. This study aims to determine what marketing strategies are used to promote donuts from Donutday. This study uses qualitative analysis which uses literacy studies from previous journals and searches for data through sources, the data obtained are obtained from interviews with business owners. The marketing strategy carried out in this business is a transactional marketing strategy, marketing strategy, strategy through social media, interactive marketing strategy, content marketing. The results of the study show marketing strategies using Instagram social media and also utilizing the features of the application to find customers. The reason for using Instagram social media is because Instagram is very popular among millennials and the features provided are quite a lot, so business actors can be creative in creating content to attract consumer interest. Keywords : selling, pandemic, UMKM, social media. References Dian Pradini, S. (2020). Media Sosial Periklanan Instagram. Sleman: Deepublish. Hasanah, h. (2016). TEKNIK-TEKNIK OBSERVASI (sebuah Alternatif Metode Pengumpulan Data Kualitatif Ilmu-Ilmu Sosial). Jurnal at-taqaddum, 22. Humairaa, U. A. (2021, Agustus). Apa sih, Strategi Pemasaran Itu? Dalam U. A. Humairaa, Apa sih, Strategi Pemasaran Itu? (hal. 11). Makassar: Pustaka Taman Ilmu. Mas'adah, Asngadi,Agung Hirmantoro. (2021). Strategi Pemasaran UMKM di Masa Pandemi Covid 19 : Studi Kasus UMKM dikawasan Pondok Pesantren Darul 'Ulum Jombang . Jurnal Bisnis Pemasaran Digital , 43. Nasrullah. (2015). Media Sosial Perspektif Komunikasi,budaya,dan sosioteknologi. Bandung: Simbiosa Rekatama Media. Rabbi, C. P. (2021, Oktober). katadata.co.id. Dipetik Oktober Jumat, 2021, dari https://katadata.co.id/safrezifitria/60dd8bfdc60ea?ppkm-darurat-berlaku-omzet-umkm-diperkirakan-anjlok-60: https://www.katadata.co.id